(untitled) (Journal of Civil Engineering Researchers, 2025)
In this laboratory study, a mixed concrete design containing Portland cement type 2 with a grade of 500 kg/m3 was made. Weight loss and ultrasonic pulse velocity (UPV) tests were performed on concrete samples at a curing age of 90 days at room temperature (21 ℃) and under a temperature of 600 ℃. In order to further investigate and verify the results, scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses were performed on concrete samples at a curing age of 90 days. The results of the tests in this study were evaluated together and compared and analysed with the results of other researchers. Applying high heat to concrete samples caused a decrease in results. In this regard, in the weight loss test of concrete samples, the weight of the concrete sample decreased from 2378 to 2225 grams, which was a decrease of 72.6%, and in the UPV test, the speed of ultrasonic waves decreased from 6179 to 3411 m/s, which was a decrease of 79.44%. At the end of this study, the results of SEM and XRD analysis at room temperature and under high temperature, while coordinating with each other, overlapped with the results of the weight loss test and the ultrasonic wave velocity test in concrete samples.